The Relationship Between Emotional Intelligence and The Cognitive Study Results of Class X Student Of Kinematics Materials At Sma Negeri In District Bangko - Hilda Maulida; Menza Hendri; Nova Susanti (Universitas Negeri Yogyakarta, 2020)
This research was motivated by many people who argued that to achieve high achievement in learning, a person must have a high Intelligence Quotient (IQ) because it is a potential provision that will facilitate learning and will result in optimal learning achievement. According to Binet in Winkel (2009), the essence of intelligence is the ability to set and maintain a goal, to make adjustments to achieve that goal, and to evaluate one's condition critically and objectively. However, according to the results of research in the field of psychology, it proves that IQ is not the only factor that affects a person's learning achievement. Many other factors influence a person's learning achievement and one of them is emotional intelligence. The purpose of this study was to determine whether there is a relationship between emotional intelligence and learning outcomes of physics in class X SMA in District Bangko.Thisresearch was a descriptive quantitative correlational study. The independent variable in this study was emotional intelligence while learning outcomes were the dependent variable. Questionnaires that consisted of managing one's emotions, motivating oneself, recognizing other people's emotions or empathy, and building relationships (cooperation) with others were used to collect the data. Learning outcome test questions which consisted of measurement material, vectors, motion, and circular motion were used to measure student learning outcomes.The data analysis technique used SPSS 16.0. by testing the normality of the hypothesis, the significance, and the regression equation. The results of the data analysis showed that the coefficient value of the correlation between emotional intelligence and learning outcomes was 0.356. 0.356 less than 0.5 or close to zero means that there is a weak correlation between emotional intelligence and learning outcomes. To test the hypothesis, it was obtained tcount greater than t table or 12.042 greater than 1.977 then H0 is rejected. It can be said that there is a significant correlation between emotional intelligence and physics learning outcomes of class X students at SMA Negeri in District Bangko.